Flexural strengthening of reinforced concrete beams using hemp sheet with different wrapping configurations - Tin, Tze Jia (2016)
Reinforced concrete structure is the rigid structure of varying quality and function but they are all ageing and deteriorating over time and the structure may also found to perform unsatisfactorily for a variety of reason. Hence, the strengthening of reinforced concrete members either to increase their service life or their restoration is becoming a universal construction practice. This study investigates the flexural behaviour of reinforced concrete beams strengthened using hemp sheet with different wrapping scheme which included U wrapping, side wrapping and bottom wrapping scheme. One controlled and three strengthened beams were casted and tested under four point-load system and subjected to loading continuously until failure. The aim of this study was to determine the effect of the hemp on flexural capacity of reinforced concrete beams with different wrapping scheme and determination of the best wrapping configuration among the wrapping scheme applied. Generally, this study showed that the application of hemp sheet on the reinforced beam improved the flexural performance of the beams. The result of this study depicted that hemp sheet has providing an increase in the load carrying capacity by 21.31% with U wrapping scheme, 11.14% with side wrapping and 8.73% with bottom wrapping. Besides that, in comparison to the different wrapping scheme, the U wrapping scheme can be concluded as the better model as it’s have a more visible load carrying capacity improvement.